Quantitative ethnobotanical study of medicinal plants used by the indigenous communities of Shawal Valley, District North Waziristan, Pakistan - Rehman, Sabith; Iqbal, Zafar; Qureshi, Rahmatullah; Shah, Ghulam Mujtaba (Ethnobotany Research and Applications, 2023)
Background: The inhabitants of distant regions typically depend on traditional information of therapeutic plants to treat various disorders. The current survey was conducted to record and explore the indigenous utilization of the therapeutic plants among people dwelling in Shawal Valley, North Waziristan, Pakistan. Methods: The data was collected through semi-structured interviews and data was analyzed by using different quantitative indices viz. use value (UV), use reports (UR), relative frequency of citation (RFC), fidelity level (FL), and family importance value (FIV). Plant specimens were submitted to the Department of Botany Herbarium, Hazara University Mansehra for future records. Results: A total of108 medicinal plants belonging to 54 families were reported which were used to cure various 119 disorders. The informants documented the highest number of plants used for digestive disorders (16 spp.), followed by diarrhea (11 spp.) and cough (10 spp.). The maximum RFC value was recorded for Bergenia ciliate (0.36), followed by Berberis lycium and Ephedra gerardiana (0.35) each. The highest UV was recorded for Bergenia ciliate (0.89), followed by Ephedra gerardiana (0.87), and Punica granatum (0.85). The maximum fidelity levels values were recorded for Bergenia ciliate and Ephedra gerardiana (100%) each. Conclusions: The present study revealed that Shawal valley has an important diversity of therapeutic plants, and the use of therapeutic plant remedies is still familiar in the study area. A total of 108 therapeutic plants, related to 54 families were recorded for the treatment of 119 disorders. Thus, the study provides baseline information for further pharmacological and phytochemical screening in order to study their bioactive compounds. Keywords: Folk Knowledge, Quantitative study, Shawal valley, North Waziristan.